Bone fragility during the COVID-19 pandemic: the role of macro- and micronutrients - Antimo Moretti; Sara Liguori; Marco Paoletta; Silvia Migliaccio; Giuseppe Toro; Francesca Gimigliano; Giovanni Iolascon (Therapeutic Advances in Musculoskeletal Disease, 2023)
Bone fragility is the susceptibility to fracture due to poor bone strength. This condition is usually associated with aging, comorbidities, disability, poor quality of life, and increased mortality. International guidelines for the management of patients with bone fragility include a nutritional approach, mainly aiming at optimal protein, calcium, and vitamin D intakes. Several biomechanical features of the skeleton, such as bone mineral density (BMD), trabecular and cortical microarchitecture, seem to be positively influenced by micro- and macronutrient intake. Patients with major fragility fractures are usually poor consumers of dairy products, fruit, and vegetables as well as of nutrients modulating gut microbiota. The COVID-19 pandemic has further aggravated the health status of patients with skeletal fragility, also in terms of unhealthy dietary patterns that might adversely affect bone health. In this narrative review, we discuss the role of macro- and micronutrients in patients with bone fragility during the COVID-19 pandemic.